Client Experience with the Ontario Birth Center Demonstration Project. (18th December 2020) - Reszel, Jessica; Weiss, Deborah; Darling, Elizabeth K.; Sidney, Dana; Van Wagner, Vicki; Soderstrom, Bobbi; Rogers, Judy; Holmberg, Vivian; Peterson, Wendy E.; Khan, Bushra M.; Walker, Mark C.; Sprague, Ann E.
Abstract : Introduction: In 2014, 2 new freestanding midwifery‐led birth centers opened in Ontario, Canada. As one part of a larger mixed‐methods evaluation of the first year of operations of the centers, our primary objective was to compare the experiences of women receiving midwifery care who intended to give birth at the new birth centers with those intending to give birth at home or in hospital. Methods: We conducted a cross‐sectional survey of women cared for by midwives with admitting privileges at one of the 2 birth centers. Consenting women received the survey 3 to 6 weeks after their due date. We stratified the analysis by intended place of birth at the beginning of labor, regardless of where the actual birth occurred. One composite indicator was created (Composite Satisfaction Score, out of 20), and statistical significance ( P < .05) was assessed using one‐way analysis of variance. Responses to the open‐ended questions were reviewed and grouped into broader categories. Results: In total, 382 women completed the survey (response rate 54.6%). Half intended to give birth at a birth center (n = 191). There was a significant difference on the Composite Satisfaction Scores between the birth center (19.4), home (19.5), and hospital (18.9) groups ( P < .001). Among women who intended to give birth in a birth center, scores were higher in the women admitted to the birth center compared with those who were not ( P = .037). Overall, women giving birth at a birth center were satisfied with the learners present at their birth, the accessibility of the centers, and the physical amenities, and they had suggestions for minor improvements. Discussion: We found positive experiences and high satisfaction among women receiving midwifery care, regardless of intended place of birth. Women admitted to the birth centers had positive experiences with these new centers; however, future research should be planned to reassess and further understand women's experiences.